1971
DOI: 10.1126/science.172.3989.1248
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Methylation of Inorganic Mercury with Methylcobalamin, a Vitamin B 12 Analog

Abstract: Chemical methylation of mercuric chloride with methylcobalamin has been studied. Methylated mercury was detected by gas chromatography; and analysis of the products of the reaction by thin-layer chromatography revealed that the methylation proceeded at a remarkably high rate when methylcobalamin and inorganic mercury were mixed. Dimethylmercury was an initial product of the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(43 citation statements)
references
References 7 publications
0
43
0
Order By: Relevance
“…One of the earliest and best-known examples of environmental mercury poisoning occurred in Japan in 1953 with the first reported cases of « Minamata disease » [1]. Despite the recognition of the toxicity of mercury and mercury vapour in the 17 th century in the Almadén (Spain) mercury mines, Minamata was the first identified example of the in situ methylation and bioaccumulation of mercury in fish.…”
Section: Introductionmentioning
confidence: 99%
“…One of the earliest and best-known examples of environmental mercury poisoning occurred in Japan in 1953 with the first reported cases of « Minamata disease » [1]. Despite the recognition of the toxicity of mercury and mercury vapour in the 17 th century in the Almadén (Spain) mercury mines, Minamata was the first identified example of the in situ methylation and bioaccumulation of mercury in fish.…”
Section: Introductionmentioning
confidence: 99%
“…17 -20 It has also been demonstrated that arsenite methylation by CH 3 -B 12 and glutathione in vitro does not require an enzyme. 20,21 These groups also reported the enhancement of the abiotic arsenic methylation by the addition of selenium(IV).…”
Section: Introductionmentioning
confidence: 93%
“…There have been a number of reports suggesting a connection between CH 3 -B 12 and arsenite methylation. McBride and Wolfe 13 studied whether CH 3 -B 12 functioned as the methyl donor in the biosynthesis of dimethylarsine from arsenate or arsenite in cell extracts of a certain methanogenic Archaea.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The degradation of thimerosal (TM) involves creation of ethylmercury cation (CH 3 CH 2 Hg + ) [6][7][8][9][10]. Further metabolism of EtHg + intermediate in-cludes stage of dealkylation to inorganic form of mercury Hg 2+ ion [11,12], which can be followed by its methylation to methylmercury form with B12 participation [13][14][15]. Mercury and its organic and inorganic forms are well recognized as the highly toxic substances [16,17] for which the primary target is the central nervous system [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%